Storm-time longitudinally propagating asymmetric modes at low latitudes - Singh, A. K.; Sinha, A. K.; Rajaram, R.; Pathan, B. M. (My University, 2012)
The westward flowing toroidal ring current at about 2–7 RE in the Earth's equatorial plane consists of symmetric and asymmetric parts. Zonal mean of H disturbances from longitudinally distributed low latitude stations represents the symmetric contribution, whereas departure from the zonal mean gives local time dependent asymmetric component at each of the stations. Through a standard analysis of closely spaced low latitude geomagnetic data we demonstrate 24 h periodicity in the asymmetric component of the storm-time ring current, which is related to the changing local time due to rotation of the Earth. Detailed examination of shorter period oscillations, when observed globally, often show westward propagating modes. Eastward propagating mode was also observed in one case. Based on satellite and radar observations covering a narrow longitude region, westward and eastward propagating modes had been reported in earlier studies. In this study, we report that similar propagating modes which are available on global scale, can be identified using ground-based magnetometer data. These globally propagating modes, observed from ground-based studies, find obvious practical application in diagnostics of the magnetosphere, especially the ring current region. Simultaneous use of satellite and ground-based data should establish the morphology of such modes.
Keywords: Magnetospheric physics; Solar wind-magnetosphere interactions; Storms and substorms